(untitled) - Buzan, Tony. (New York, 1974)
Using the latest research on the workings of the human brain, Buzan provides step-by-step exercises for discovering the powers of the right side of the brain and learning to use the left side more effectively. By increasing our understanding of how the mind works, Buzan shows us how to use our brains to the best advantage.
Keywords: Study skills,Thought and thinking,Memory,Creative ability